Identifying polymorphisms in the Alzheimer's related APP gene using the MinION sequencer - Brookes, Keeley (OMICS International, 2016)
The MinION is a bench top sequencer by Oxford nanopore technologies (ONT) that allows long reads of DNA sequence. Few studies have tested whether polymorphisms can be detected using this device. Several polymorphisms within the APP gene were used to test this capability. Library preparation and sequencing were performed using standard ONT protocols for samples harbouring ive different mutations. Alignments to the reference sequence were analysed in MinoTour and basecalls were manually investigated using proportion of reference calls between samples to identify the variants. MinoTour’s algorithm for variant detection was unable to identify the polymorphisms due to high base calling error rate. By calculating the difference in reference basecall proportions along the amplicon, it was possible to identify the polymorphisms above a Bonferroni-corrected threshold (p<1 × 10-4). The MinION has potential for polymorphism detection when comparing samples; however careful interpretation is needed as high base calling error rates can mask the presence of polymorphisms.